Efeito da suplementação com ácido ascórbico em pacientes em tratamento para desintoxicação por uso de substâncias psicoativas - Queiros, Juliana Pereira (2024)
Substance Use Disorders are a widely discussed phenomenon, having become a serious social and public health issue. In this context, the present study aimed to analyze the effect of vitamin C supplementation on patients undergoing detoxification from psychoactive substances at a Mental Health Hospital in Fortaleza, Brazil. This clinical, randomized, and controlled study involved 69 patients undergoing detoxification treatment. Participants were divided into three groups: two intervention groups receiving daily vitamin C supplementation at doses of 500 mg and 1000 mg, respectively, and a control group receiving a placebo. The study lasted 10 days. It is noteworthy that only 31 patients completed the treatment (11 - 1000 mg SUP; 10 - 500 mg SUP; 10 - CONTROL). The methodology included biochemical laboratory parameters, application of psychological scales (Beck Anxiety and Depression Scales), levels of oxidative stress markers before and after the intervention period (D1 and D10), and anthropometric data collected at the start (D1), middle (D5), and end (D10) of the treatment. Additionally, a socioeconomic profile questionnaire was administered. Results indicated that mental and behavioral disorders due to multiple drug use (ICD F19) were the most common (82.6%). The main reason for hospital discharge was patient-initiated discharge (89.47% of discharges), reflecting a characteristic of the Detoxification Unit. Regarding the number of admissions, 40.58% of patients had between two and four admissions, and 33.33% had more than eight admissions. Concerning religiosity, 30.76% of patients were Catholic, 52.3% were Evangelical, and 12.3% were Atheists. There was a predominance of patients with low educational attainment and family income, with most patients' parents also having low educational levels. Catholic patients had the highest treatment completion rate (55%), followed by Evangelicals (47%). A significant difference was observed in BMI between the 500 mg and 1000 mg supplementation groups, with the 1000 mg group having a higher BMI. The same pattern was observed in Waist Circumference, Hip Circumference, and Abdominal Circumference. No differences were observed in depression or anxiety scales between the groups concerning the type of supplementation provided, although improvements were noted in scores between the first and second assessments. Additionally, no differences were observed between the groups in the oxidative stress analysis (nitrite, reduced glutathione, and TBARS), although there was a reduction in nitrite between the first and second assessments. Positive results were found in the biochemical profile with increased serum calcium, HDL cholesterol, and potassium in the supplemented groups, as well as a reduction in leukocytes, neutrophils, and segmented cells, though still within normal limits (1000 mg SUP group). Thus, vitamin C may play a beneficial role for the studied population, suggesting improvements in inflammation, lipid profile, and absorption of certain minerals.